Design and Teaching Process of Stem Project "Smart Night-Lamp" for High School Students - Huy, Tran Quang; Khanh, Pham Quoc; Tuan, Nguyen Ngoc; Thong, Nguyen Duc; Theu, Luong Thi (VNU Journal of Science: Education Research, 2023)
In Vietnam general education curriculum 2018, a learning model called STEM education is being interested in and encouraged in teaching and learning. Choosing a STEM topic will  engage students to explore knowledge. The  topics which selected need to be linked to reality and have a direct impact on human life. In the era of industry 4.0, besides data science, machine learning, artificial intelligence, etc., the role of automation is indispensable. The previously developed STEM topics are quite diverse, including topics on physics, chemistry, biology, informatics, etc. However, STEM topics about automatic control field are rarely exploited to increase students' awareness of the role of automation in life in the era of technology revolution 4.0, and also enrich the topics of learning and experience in the contents of smart home, warning system, etc. in the general education program issued in 2018. In this paper, therefore, we propose a new STEM project in the field of smart models, which is the smart night-lamp. Furthermore, we use the 6E teaching model to design the teaching process, which emphasis on two elements of technical design and practice in STEM-oriented teaching. After proposing a new STEM topic and designing a teaching process according to the 6E process, we also conducted a pedagogical experiment to ensure the feasibility of the proposed topic in STEM education.